MANAGEMENT OF FELINE DYSTOCIA DUE TO UTERINE RUPTURE IN CIKAL PET CARE, POLEWALI MANDAR, WEST SULAWESI: A CASE REPORT - Muhammad Ayub; Filzah Fahrana Mulya; Tomy Y. Suwito; Muh. Haikal Ramadhan; Gilang Ramadhan; Isnaniah Bagenda; Iis Syamsiah; Riska Wahyuni Alwi; Nurul Fuady Abbas; Wismoyo (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
The trend of cat ownership in the community continues to increase along with the growing interest in companion animals; however, this condition is not free from various reproductive medical problems. One of the disorders frequently encountered is difficulty in parturition, or dystocia, which may lead to serious complications if not managed promptly and appropriately. Dystocia is a reproductive emergency in cats that can progress to uterine rupture if not treated adequately. This case report aims to describe the clinical findings, diagnostic approach, and surgical management of a cat with dystocia accompanied by uterine rupture. The method used was a case report based on anamnesis, physical examination, and abdominal palpation, with confirmation through intraoperative findings during exploratory laparotomy, considering the limitations of supporting diagnostic examinations. The examination results revealed abdominal enlargement, dehydration, and the presence of free fetuses within the abdominal cavity due to rupture of the uterine wall. Management was performed through total ovariohysterectomy accompanied by abdominal lavage and postoperative therapy. It is concluded that a combination of careful clinical diagnosis and immediate surgical intervention is an effective approach in managing cases of dystocia complicated by uterine rupture in cats.